SWEAR WORDS SPOKEN BY THE CHARACTERS OF HOW I MET YOUR MOTHER – SEASON 1 - PUSPITA, ERAI SAFIRA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Swear words, sociolinguistics, How I Met Your Mother. Swear words are the informal words that are used by people to express their emotion in terrible situation. In this research, a deep analysis is conducted towards American habit of swearing as reflected in a series How I Met Your Mother (HIMYM) Season 1. HIMYM is a popular series from USA that tells about friendship of five characters in modern era, in the middle of New York. Since they live in a modern era in which swearing is no longer considered as taboo, many swear words are uttered in their interaction. The problem in this study is formatted to find kinds of swear words by all characters in HIMYM.Descriptive method is used in this research, starting by watching the movie, finding the transcript from the internet, finding swear words to be analyzed, and givng notes about the occurences and habit of swearing of each characters. The data are taken from HIMYM Season 1 that consists of 22 episodes. Theories of swear words and Sociolinguistics in general are employed here to give clearer and appropriate analysis towards the characters’ habit in swearing.It is found that in HIMYM Season 1, swearing has been a habit of all characters. No single episode in this season ended without the occurence of swear words. Each characters in this series also has different habit in swearing. Some of them are Lily Aldrin who is a kindergarten teacher but has the highest frequency of swearing among other characters, and also Robin Scherbatsky who eventhough has average frequency of swearing but always says it by using Divine’s name (God, Gosh). The result of this analysis can give broad imagery about the habit of swearing among American people.  From the study, it is concluded that swear words are used by people to express their emotion. It is also hoped that this study may broaden the scope of research on Sociolinguistics fields.